Seasonal Anomalies between S&P CNX Nifty Shariah Index and S&P CNX Nifty Index in India - Dharani, M. (Journal of Social and Development Sciences, 2011)
The present study compares the risk and return of the Nifty Shariah index and Nifty index at days, months and quarters wise during the period 2nd January 2007 to 31st December 2010. The raw returns of the both indices are calculated as today price minus yesterday price divided by yesterday price. The t- test has been used to test the mean returns difference between both indices. The average Monday return of the Nifty Shariah index is compared with average return of the Nifty index by using two sample t-test. Like that, the average returns of the remaining of the days of Nifty Shariah index are compared with average returns of remaining days of the Nifty Index. The study finds that there is no difference between average day -wise returns of the Nifty Shariah index and average day return of the Nifty Index during the study period. The study also compares the average January return of the Nifty Shariah index with average January return of the Nifty index, average February return of the Nifty Shariah index with average return of the Nifty index and so on. Finally, the average return of the first, second, third and fourth quarter of Nifty Shariah with average return of the respective first, second, third and fourth quarter of Nifty index are compared. The study finds that there is a significant difference between average return of the Nifty Shariah and Nifty indices in the month of July and September. It is derived from the study that the Muslim Investors are evincing more interest to sell the shares in the market from July to September. The reason being, expenses inconnection with Ramalan Festival during that period. Therefore, the study confirms that Ramalan effect have been prevailing in the Indian Stock Market. Thus, this study reveals that the seasonal variation exits very much in Shariah Index